Menopause Across Cultures and Contexts : A Comparative Study of Symptoms, Supportive Networks, and Workplace Experiences in Germany and the USA - Junghae Yun (2024)
Aim: This study aims to comprehensively explore menopause-related experiences, perceptions, and support networks in both Germany and the U.S., encompassing broader societal contexts and workplace dynamics. Methods: Employing an explorative and descriptive design rooted in quantitative cross-sectional research, data was collected through online surveys, with 500 participants from each country, during specified periods from September 6th to 16th, 2022, and January 20th to February 8th, 2023. Results: Our comparative analysis reveals intriguing distinctions in menopausal experiences, with German women reporting twice as many symptoms yet expressing less positivity about their journey compared to their U.S counterparts. Moreover, German women feel less supported in the daily life and workplace and are more reluctant to share their menopause experiences compared to their counterparts in the U.S However, German women report experiencing less discrimination and workplace challenges, despite having less time off entitlement and support networks than their U.S counterparts. This study contributes valuable insights into the nuanced landscape of menopause experiences across diverse cultural and work environments, with implications for healthcare provision, workplace policies, and societal attitudes towards menopause.